2021
DOI: 10.3390/mi12030304
|View full text |Cite
|
Sign up to set email alerts
|

Bionic Organs: Shear Forces Reduce Pancreatic Islet and Mammalian Cell Viability during the Process of 3D Bioprinting

Abstract: Background: 3D bioprinting is the future of constructing functional organs. Creating a bioactive scaffold with pancreatic islets presents many challenges. The aim of this paper is to assess how the 3D bioprinting process affects islet viability. Methods: The BioX 3D printer (Cellink), 600 μm inner diameter nozzles, and 3% (w/v) alginate cell carrier solution were used with rat, porcine, and human pancreatic islets. Islets were divided into a control group (culture medium) and 6 experimental groups (each subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…To determine the sear stress imposed to the islet during the GSIS-assay protocol, the flow in the main serpentine channel was modeled using COMSOL Multiphysics. While it has already been shown that microfluidic continuous perifusion positively affects islets function and survival (Sankar et al, 2011) , too high shear stress can cause cell deformation and lead to permanent damage (Klak et al, 2021) . To model our experimental conditions, atmospheric pressure was assigned at the inlet wall and a flow rate of 100 μL/min or 2.5 μL/min was assigned at the outlet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the sear stress imposed to the islet during the GSIS-assay protocol, the flow in the main serpentine channel was modeled using COMSOL Multiphysics. While it has already been shown that microfluidic continuous perifusion positively affects islets function and survival (Sankar et al, 2011) , too high shear stress can cause cell deformation and lead to permanent damage (Klak et al, 2021) . To model our experimental conditions, atmospheric pressure was assigned at the inlet wall and a flow rate of 100 μL/min or 2.5 μL/min was assigned at the outlet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In islet 3D bioprinting, it is essential to optimize the shear stress (pressure, nozzle diameter, printing speed), which can reduce cell viability by up to 40-85%. Klak and colleagues found that comparing with the large size islets, smaller size human islets (50-100 μm) have survival advantage under the same mechanical pressures, and the optimal pressure by the extrusion method should be lower than 30 kPa while using 3% (w/v) alginate as a carrier 150 . In a microfluidic platform, the shear stress is determined by flow rate and affects the morphology and function of islet organoids 56 .…”
Section: Mechanical Stimulation In the Construction Of Human Islet Or...mentioning
confidence: 99%
“…In addition, extrusion-based bioprinting can be adapted to create vascular structures with coaxial nozzles. Despite the advantages and successes, the drawbacks are relatively obvious, such as a low print resolution [ 122 ] and shear force affecting cell viability [ 123 ]. To solve the poor extrusion printability of dECM bioinks, the use of multiple material composite, especially nanoparticles, has become a widespread approach.…”
Section: 3d Bioprinting Technologiesmentioning
confidence: 99%